2006
DOI: 10.1124/mol.105.021261
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of p53 Blockage by the A2AAdenosine Receptor via a Novel Interacting Protein, Translin-Associated Protein X

Abstract: Blockage of the p53 tumor suppressor has been found to impair nerve growth factor (NGF)-induced neurite outgrowth in PC-12 cells. We report herein that such impairment could be rescued by stimulation of the A 2A adenosine receptor (A 2A -R), a G protein-coupled receptor implicated in neuronal plasticity. The A 2A -R-mediated rescue occurred in the presence of protein kinase C (PKC) inhibitors or protein kinase A (PKA) inhibitors and in a PKA-deficient PC-12 variant. Thus, neither PKA nor PKC was involved. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 68 publications
1
66
1
Order By: Relevance
“…The proproliferative characteristic of this receptor is consistent with other reports that show increased endothelial cell proliferation upon its activation (52). This is in contrast to studies in other cell types, including PC12 (pheochromocytoma) and smooth muscle cells, where decreased proliferation upon activation of adenosine A 2A receptor was observed (52,53). In other studies with PC12 cells, there was a decrease in cell viability upon activation of the receptor in one study (54), whereas inhibition of apoptosis was observed in another (55).…”
Section: Discussioncontrasting
confidence: 53%
“…The proproliferative characteristic of this receptor is consistent with other reports that show increased endothelial cell proliferation upon its activation (52). This is in contrast to studies in other cell types, including PC12 (pheochromocytoma) and smooth muscle cells, where decreased proliferation upon activation of adenosine A 2A receptor was observed (52,53). In other studies with PC12 cells, there was a decrease in cell viability upon activation of the receptor in one study (54), whereas inhibition of apoptosis was observed in another (55).…”
Section: Discussioncontrasting
confidence: 53%
“…An alternative explanation of this phenomenon could be that the A 2B receptor protein interacts with other signaling pathways unrelated to adenosine. Recent evidence suggests that adenosine receptors play a role in the assembly of multiprotein signaling complexes (Sitaraman et al, 2002;Gsandtner et al, 2005;Pacheco et al, 2005;Milojevic et al, 2006;Sun et al, 2006a). Rearrangement of proteins normally coupled to the A 2B receptor as a result of the A 2B knockout may affect regulation of TNF-␣ synthesis or release.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative and more likely explanation of this phenomenon could be that the A 2B receptor protein interacts with other signaling pathways unrelated to adenosine. Recent evidence suggests that adenosine receptors play a role in assembly of multiprotein signaling complexes (57)(58)(59)(60)(61). Rearrangement of proteins normally coupled to the A 2B receptor as a result of the A 2B KO may affect FcRI-dependent regulation of degranulation.…”
Section: Discussionmentioning
confidence: 99%